This is an EVEN function
The definition of an even function is for all 'x',:
f(-x) = f(x). This means that all negative 'x' values of the function have f(x) values the same as their corresponding positive 'x' value [i.e. for the above case f(-1) = f(1) = 5]
To prove this, plug in -x for x in the function:
f(-x) = (-x)^4 + (-x)^2 + 3 -------> x^4 + x^2 + 3
Since f(-x) = f(x) = x^4 + x^2 + 3, this is an EVEN function
In general, polynomials with an even power are EVEN functions (i.e. x^2, x^4, x^6.....) whereas polynomials with odd powers are ODD functions (i.e. x, x^3, x^5.....)
ODD functions are defined as:
f(-x) = -f(x)
--------
Hope this helps
2006-12-14 11:42:25
·
answer #1
·
answered by JSAM 5
·
1⤊
1⤋
An odd function does not mean that the results are always even or odd. If that's what it meant, this would be an odd function. However the definition of an odd function given by the first answer is correct and therefore this is an even function.
2006-12-14 11:47:08
·
answer #2
·
answered by c_a_cudmore 2
·
0⤊
1⤋
f(-x)=x^4 + x^2 + 3 = f(x)
so f(x) is an even function
2006-12-14 11:49:49
·
answer #3
·
answered by James Chan 4
·
0⤊
2⤋
Odd. The last +3 gives it away.
2006-12-14 11:44:50
·
answer #4
·
answered by Anonymous
·
0⤊
3⤋
a million: Even #2: consumer-friendly HOW: Even: f(x) = f(-x) consumer-friendly: f(-x) = -f(x) attempt #a million: f(x) = 2x² - 3 f(-x) = 2(-x)² - 3 = 2x² - 3............... (when you consider that unfavorable decision squared are an same as their opposite squared) hence, it truly is even. attempt #2 f(x) = -2x^3 + 8x = x( 8 - 2x²) f(-x) = -x( 8 - 2(-x)² ) = -x( 8 - 2x²) = -f(x) hence, it truly is consumer-friendly.
2016-11-26 20:01:14
·
answer #5
·
answered by ? 4
·
0⤊
0⤋